Autologous transplantation of adult adipose derived stem cells into rabbit urethral wall - Almeida, Fernando Goncalves; Dantas Nobre, Yuri Tulio; Leite, Katia R. [UNESP]; Bruschini, Homero [UNESP] (Springer London Ltd, 2010)
A study was carried out to evaluate the feasibility of autologous adipose derived stem cells (ADSC) transplantation into female rabbits' urethra walls as an alternative to intrinsic urethral regeneration.Inguinal fat pad of 12 New Zealand adult female rabbits were harvested and processed to obtain stromal vascular fraction (SVF). The SVF were platted to isolate ADSC. Before urethral injection, cells were labeled with DiI marker. The urethra wall was injected with 1 x 10(7) autologous cells or saline (sham). The urethra was harvested at 2, 4, and 8 weeks to identify DiI-labeled cells.At 2 and 4 weeks, the ADSCs create a nodule localized in the urethral sub-mucosa. At 8 weeks, the ADSCs spread and integrated with the urethra wall from the initial injection site.This is the first study to demonstrate a successful autologous ADSCs transplantation. It confirms that ADSCs can survive and integrate within the urethral wall.
Keywords: Adult stem cell; Animal model; Bladder; Tissue engineering; Urethra wall; Urinary incontinence